La-related protein 1 (LARP1) repression of TOP mRNA translation is mediated through its cap-binding domain and controlled by an adjacent regulatory region - Philippe, Lucas (Nucleic Acids Res, 2018)
Cell growth is a complex process shaped by extensive and coordinated changes in gene expression. Among these is the tightly regulated translation of a family of growth-related mRNAs defined by a 5′ terminal oligopyrimidine (TOP) motif. TOP mRNA translation is partly controlled via the eukaryotic initiation factor 4F (eIF4F), a translation factor that recognizes the mRNA 5′ cap structure. Recent studies have also implicated La-related protein 1 (LARP1), which competes with eIF4F for binding to mRNA 5′ ends. However, it has remained controversial whether LARP1 represses TOP mRNA translation directly and, if so, what features define its mRNA targets. Here, we show that the C-terminal half of LARP1 is necessary and sufficient to control TOP mRNA translation in cells. This fragment contains the DM15 cap-binding domain as well as an adjacent regulatory region that we identified. We further demonstrate that purified LARP1 represses TOP mRNA translation in vitro through the combined recognition of both the TOP sequence and cap structure, and that its intrinsic repressive activity and affinity for these features are subject to regulation. These results support a model whereby the translation of TOP mRNAs is controlled by a growth-regulated competition between eIF4F and LARP1 for their 5′ ends.